2017
DOI: 10.1080/14606925.2017.1352757
|View full text |Cite
|
Sign up to set email alerts
|

Persuasive Technology as key to increase Working Health Condition. The Case study of a Wearable System to prevent Respiratory Disease

Abstract: According to occupational disease registries and voluntary reporting schemes in various European countries, the annual incidence of respiratory diseases is estimated to be 2– 5 cases per 100 000 working individuals. Nowadays the use of personal protective equipment is the only way for workers to prevent disease but it is highly sparse. Authors suggest the development of a wearable novel system that, exploiting persuasive technologies can build an environmental sensing networks to share information about user h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…This is based on the persuasive technology theory 67 to achieve desirable change by reinforcing behaviour and attitude of health and wellness. 68 This theory is able to affect users’ emotions and build trust in the technology so that they will integrate technology into their daily lives and continue to use it for a long period. 69 …”
Section: Methodsmentioning
confidence: 99%
“…This is based on the persuasive technology theory 67 to achieve desirable change by reinforcing behaviour and attitude of health and wellness. 68 This theory is able to affect users’ emotions and build trust in the technology so that they will integrate technology into their daily lives and continue to use it for a long period. 69 …”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, although only a few studies are working on wearable technology, at least Ferraro et. al [23] incorporate persuasive and wearable design principles in their persuasive wearable system. The system is intended to motivate the workers to wear personal protective equipment (PPEs) and increase their awareness regarding work-related risks and health status.…”
Section: Implication Of Design Principles In Designing Wearable Persu...mentioning
confidence: 99%
“…From the pre-analysis, it can be concluded that most previous studies were found focusing on the health [7], [20][21], [22][23][24][25][26], education [18][19], [21], [27][28][29][30][31][32][33], and environmental [34][35] context. On top of that, it was observed that the trend of technology used is computer-based [17][18][19], [21], [28][29][30], [32][33], [35], mobile [20], [22][23][24][25], [26][27], [33] and wearable [7], [23][24], [31]. Moreover, most previous studies intended to change users' behaviour with various target outcomes.…”
Section: Comparative Analysismentioning
confidence: 99%
“…The last INAIL (Istituto Nazionale Assicurazione Infortuni sul Lavoro) report on occupational diseases showed that the working places with the highest percentage of respiratory diseases are agriculture, manufacturing and transportation sectors [22].…”
Section: Problem Identifying: Empathy Phasementioning
confidence: 99%